2016
DOI: 10.1002/gps.4631
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the neuropsychological profiles of people living in squalor without hoarding to those living in squalor associated with hoarding

Abstract: Preliminary evidence suggests that squalor associated with hoarding may have distinct neuropsychological features compared against squalor only. Future work should be conducted using a larger sample and a common neuropsychological battery to better understand the deficits associated with hoarding-related squalor. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Squalor can occur with or without hoarding. A study by Lee et al . found that patients who live in squalor without hoarding tended to be younger (mean age 69.9 years).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Squalor can occur with or without hoarding. A study by Lee et al . found that patients who live in squalor without hoarding tended to be younger (mean age 69.9 years).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The environment inhabited by people with hoarding behaviours can deteriorate into squalor if extensive clutter impedes cleaning efforts. They tend to present at a later age (mean age 75.8 years), usually due to loss of a domestic partner, onset of frailty or neurocognitive disorders …”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations